The levels of pyruvate kinase activity in renal and hepatic tissues of rats with diabetes induced by streptozotocin - Yilmaz, S; Üstündag, B (Scientific Technical Research Council Turkey, 2002)
In this study, the changes in pyruvate kinase enzyme activities in the liver and kidney tissues of rats with diabetes induced by streptozotocin were examined and the relations with the disease were investigated. Diabetes mellitus was induced in Wistar-Albino rats by the administration of a single intraperitoneal dose of streptozotccin (60 mg/kg body weight). After streptozotccin was injected, the pyruvate kinase activities in the livers and kidneys of the rats were analysed according to Beutler's method on days 3 and 12. It was determined that liver pyruvate kinase enzyme levels in rats with diabetes induced with streptozotocin were decreased on days 3 and 12 in relation to the value obtained from the control group (p<0.01). Pyruvate kinase activity in kidney on day 3 in the diabetic group were not significantly different from that of the control group. However, on day 12 there were significantly higher pyruvate kinase levels in the kidneys of the diabetic group than in those of the control group (p<0.001). In conclusion, it was observed that in diabetes mellitus, pyruvate kinase activities varied according to different days as a result of abnormalities in the carbohydrate metabolism.
Streptozotosin ile diabet oluşturulan ratlarin karaci?er ve böbrek dokularinda pirüvat kinaz aktivite düzeyleri
Keywords: kidney; liver; pyruvate kinase; streptozotocin